Pelayanan Tuan Rumah Homestay dalam Mendukung Pengembangan Pariwisata Berbasis Masyarakat (Community Based-Tourism) di Desa Wisata Wates Jaya, Kabupaten Bogor - Rustini Rustini (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2021)
During pandemic, people still want to take some vacation. Desa wisata is an alternative of tourism destinations to go without connecting to many people simultaneously. Spending time by staying at homestay is an alternative way for tourists to do their vacations. The purpose of this study was to know how the service of homestay’s host gave its support to the development of community based-tourism in Desa Wisata Wates Jaya, Kabupaten Bogor. This study was conducted by using Purposive Sampling sample technique and descriptive-qualitative method which will result in findings without the assistance of statistical procedure or form of calculations in its analysis. The primary data of this study wascarried out through interviews and observation. While secondary data was taken from various written sources and documentation. The theory used was according to Zithaml dan Bitner (1996), that service has 5 (five) aspects, namely reliability, assurance, tangible, empathy and responsiveness. The result of this study could be concluded that the service of homestay’s host in supporting the development of community based-tourism in Desa Wisata Wates Jaya, Kabupaten Bogor wasconsidered still had lacks of the 5 aspects mentioned-above